2019
DOI: 10.1111/jcmm.14282
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial implications in human pregnancies with intrauterine growth restriction and associated cardiac remodelling

Abstract: Intrauterine growth restriction (IUGR) is an obstetric complication characterised by placental insufficiency and secondary cardiovascular remodelling that can lead to cardiomyopathy in adulthood. Despite its aetiology and potential therapeutics are poorly understood, bioenergetic deficits have been demonstrated in adverse foetal and cardiac development. We aimed to evaluate the role of mitochondria in human pregnancies with IUGR. In a single‐site, cross‐sectional and observational study, we included placenta a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…Previous studies have suggested that plasma CFCmtDNA and cellular mtDNA copy number reflect different cellular processes in disease conditions. Intracellular mtDNA copy number in PBMCs is thought to reflect variations in mitochondrial bioenergetics and biogenesis 62 , while CFCmtDNA is mostly associated with cellular stress and tissue damage 6 . Here, in addition to plasma CFCmtDNA concentrations, we measured mtDNA copy number in PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that plasma CFCmtDNA and cellular mtDNA copy number reflect different cellular processes in disease conditions. Intracellular mtDNA copy number in PBMCs is thought to reflect variations in mitochondrial bioenergetics and biogenesis 62 , while CFCmtDNA is mostly associated with cellular stress and tissue damage 6 . Here, in addition to plasma CFCmtDNA concentrations, we measured mtDNA copy number in PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…We found evidence of mitochondrial degeneration, i.e., mitochondrial membrane rupture, absence of mitochondrial ridges and less electron-dense mitochondrial matrix in all treated groups. Placental mitochondrial dysfunction is associated with IUGR (62,63) and may be related, at least in part, to the lower fetal weight observed in high-ZIKV-ICompetent fetuses along with the altered placental apoptotic and proliferative patterns. Furthermore, mitochondrial dysfunction together with ER stress is likely to modify the placental ROS balance and generate local oxidative stress (64), which is associated with impaired fetal development (65).…”
Section: Discussionmentioning
confidence: 99%
“…Various ETC complexes as well as their subunits such as Complexes I-IV, cytochrome c oxidase (COX), are found to be downregulated in both preeclamptic and FGR placentas [ 155 , 156 , 157 , 158 ]. Accordingly, activity of one or more of ETC complexes in the placenta is suppressed in preeclampsia and FGR [ 157 , 158 , 159 , 160 , 161 ]. However, the work from Cetin’s laboratory demonstrates that cytotrophoblast ETC activity is increased in placentas of FGR [ 162 ].…”
Section: Mitochondrial Ros and Preeclampsia/fgrmentioning
confidence: 99%